A General, Effcient and Green Procedure for Synthesis of Dihydropyrimidine‐5‐carboxamides in Low Melting Betaine Hydrochloride/Urea Mixture. Issue 6 (23rd March 2016) - Liu, Peng; Hao, Jianwu; Zhang, Zhanhui
Abstract: A simple, facile and convenient strategy has been developed for the synthesis of dihydropyrimidine‐5‐carboxamides in low melting mixture of betaine hydrochloride/urea. In this procedure, the low melting mixture of betaine hydrochloride/urea plays a triple role: as a catalyst, solvent and reactant. The present green protocol has advantages such as high yield of products, short reaction times, operational simplicity, no chromatographic separation, eco‐friendliness, and applicability for large‐scale synthesis. Abstract : Dihydropyrimidine‐5‐carboxamide derivatives were effectively synthesized in low melting mixture of betaine hydrochloride/urea. In this procedure, the low melting mixture of betaine hydrochloride/urea plays a triple role: as a catalyst, solvent and reactant.